Understanding the Contributions of Trait Autism and Anxiety to Extreme Demand Avoidance in the Adult General Population. - White, Rhianna; Livingston, Lucy A.; Taylor, Emily C.; Close, Scarlett A. D.; Shah, Punit; Callan, Mitchell J. (Journal of Autism & Developmental Disorders, 2023)
Autism and anxiety are thought to be related to extreme demand avoidance (EDA), which is characterised by intense avoidance of everyday demands. However, the relative importance of autism and anxiety to EDA has yet to be investigated, and little is known about EDA in adulthood. We conducted two online survey studies (Ns = 267 and 549) with adults in the general population to establish the relative importance of autistic traits and anxiety as predictors of demand avoidance, using dominance analysis. Both autistic traits and anxiety were unique and equally important predictors of demand avoidance. These findings suggest EDA is linked to autism and are consistent with the theory that demand avoidance behaviours are potentially anxiety-driven in adults.